Health Informatics on Low Birth Rate Data - Ong, Janson; Asirvadam, Vijanth S.; Kannan, Subarmaniam; Krishnan, Suresh K. (2008)
Health Informatics is now tending to replace the previously commoner term 'medical informatics', reflecting a widespread concern to define an information agenda for health services which recognizes the role of citizens as agents in their own care, as well as the major information-handling roles of the non-medical healthcare professions. Similar work had being carried out by the present authors on school examination system and ecommerce transaction activity which indicates the application of data-mining for knowledge extraction. This prompt the present author to apply similar concepts on health based data.